Associations between age‐related macular degeneration and sleep dysfunction: A systematic review. (31st August 2022) - Sia, Josh Tjunrong; Lee, Ester P. X.; Cheung, Chui Ming Gemmy; Fenwick, Eva K.; Laude, Augustinus; Ho, Kam Chun; Fenner, Beau J.; Wong, Tien Y.; Milea, Dan; Lamoureux, Ecosse L.; Man, Ryan E. K.; Najjar, Raymond P.
Abstract: Background: Age‐related macular degeneration, a prevalent degenerative retinal disease, is associated with non‐visual and psychosocial impairments that may affect sleep. In this systematic review, we evaluated associations between age‐related macular degeneration (AMD) and sleep, highlighted knowledge gaps and provided evidence‐based recommendations to clinicians to enable holistic management of AMD patients. Methods: We searched PubMed, Embase and the Cochrane Central registries for papers published before May 2022. Non‐English, qualitative studies and grey literature were excluded. Studies evaluating the association between AMD and sleep (including sleep disorders like insomnia and sleep apnea), and vice versa, were included. The quality of shortlisted studies was evaluated using the Newcastle Ottawa Scale. Results: Six (two case–control studies, three longitudinal cohort studies and one cross‐sectional study) of 551 studies were included in this review. Four studies found that AMD was associated with increased rates of sleep apnea and poorer reported sleep quality, while five studies showed that patients with sleep apnea or insomnia were at higher risk of developing AMD. Associations between self‐reported sleep quantity and AMD were conflicting. No study evaluated the relationship between AMD and sleep using objective sleep assessment tools. Conclusion: Only a limited number of studies investigated associations between AMD and sleep. These studies suggest a bidirectional relationship between AMD and sleep dysfunction yet disagree on the relationship between sleep quantity and the likelihood of AMD. Additional studies, using objective characterisation of sleep in patients with AMD are required to confirm these findings.